2019
DOI: 10.1111/1556-4029.14098
|View full text |Cite
|
Sign up to set email alerts
|

Forty‐Three Fatalities Involving the Synthetic Cannabinoid, 5‐Fluoro‐ADB: Forensic Pathology and Toxicology Implications

Abstract: Forty‐three fatalities involving the potent synthetic cannabinoid, 5‐Fluoro‐ADB, are summarized. For each case, a description of the terminal event, autopsy findings, cause of death, qualitative identification of 5‐Fluoro‐ADB and its ester hydrolysis metabolite, 5‐Fluoro‐ADB metabolite 7, in urine, and the quantitative values obtained in the blood specimens are outlined. Central blood concentrations ranged from 0.010 to 2.2 ng/mL for 5‐Fluoro‐ADB and 2.0 to 166 ng/mL for 5‐Fluoro‐ADB metabolite 7. Peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
0
18
1
Order By: Relevance
“…Reports on the identification of synthetic cannabinoid metabolites in blood are currently limited, but awareness of the necessity of this practice appears to be increasing. In the instance of 5F‐ADB, multiple reports on the identification of M5 in blood have been published 39–42,45,50 . The authors only found one published report, by Kraemer et al, 43 mentioning the identification of M1 in blood and this did not provide detailed analysis of M1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reports on the identification of synthetic cannabinoid metabolites in blood are currently limited, but awareness of the necessity of this practice appears to be increasing. In the instance of 5F‐ADB, multiple reports on the identification of M5 in blood have been published 39–42,45,50 . The authors only found one published report, by Kraemer et al, 43 mentioning the identification of M1 in blood and this did not provide detailed analysis of M1.…”
Section: Resultsmentioning
confidence: 99%
“…In the instance of 5F-ADB, multiple reports on the identification of M5 in blood have been published. [39][40][41][42]45,50 The authors only found one published report, by Kraemer et al, 43 mentioning the identification of M1 in blood and this did not provide detailed analysis of M1. The current report supplements this work, and provides the first detailed report on the presence of M1 in blood in the absence of the parent 5F-ADB compound.…”
Section: Identification Of Predominant Metabolites In Authentic Hummentioning
confidence: 99%
See 2 more Smart Citations
“…However, the NPS, especially the synthetic cannabinoids (SC) have gained increasing popularity both in local media and media worldwide. Up to now, a lot of fatalities with SC at least contributing to the occurrence of death have already been reported (Boland et al 2019;Darke et al 2019;Kraemer et al 2019;Yamagishi et al 2018). Besides these single case reports, some systematic and few controlled animal studies have been performed to obtain information about the tissue distribution of SC (Castaneto et al 2015;Meyer 2016).…”
Section: Introductionmentioning
confidence: 99%